Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By adopting Li1+a (NixCoyMnzGb) TcO2 positive electrode active material and using high-speed physical mixing and low-speed physical mixing, the problem of insufficient structural stability of high-nickel positive electrode active material is solved, and the circulation performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411548251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The structural stability of high-nickel positive electrode active materials is insufficient, resulting in the accelerated capacity decay of the battery during long-term circulation and poor circulation performance.
Li1+a(NixCoyMnzGb)TcO2 is used as the positive electrode active material, where 0.01≤a≤0.1, 0.6≤x≤1, 0
It improves the crystal structure stability of the positive electrode active material, slows down the attenuation of battery capacity, and significantly improves the cycling performance of the battery.
Smart Images

Figure CN119419261A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, positive electrode sheets, batteries, and electrical equipment. Background Art
[0002] With the vigorous development of the new energy vehicle industry, lithium-ion batteries have attracted much attention due to their high energy density and good cycle performance. As the part with the highest cost share, the development of positive electrode active materials is also developing faster and faster. Multi-element positive electrode active materials are currently the materials with the highest commercial capacity and are widely used in power batteries. In order to prepare multi-element positive electrode active materials with higher energy density, better cycle performance and excellent safety, the development and application of high-nickel materials has become one of the current mainstream development directions. However, the structural stability of high-nickel materials still needs to be improved. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.
[0004] In a first aspect, the present application provides a positive electrode active material, wherein the positive electrode active material comprises a compound represented by formula I: Li 1+a (Ni x Co y Mn z G b )T c O 2 Formula I, wherein 0.01≤a≤0.1, 0.6≤x≤1, 0<y≤0.2, 0<z≤0.2, 0<b≤0.04, 0≤c≤0.03; G includes at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, Li, F, and P, and T includes at least one of B, Al, Sr, Si, Nb, W, Ti, Zr, La, F, and P; the characteristic peak interplanar spacing change rate Δd of the positive electrode active material (104) satisfies: 0.05%≤Δd≤0.5%, wherein Δd=(d 前 -d 后 ) / d 前 ×100%,d 前 is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by X-ray diffractometer before cycling, d 后 is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by an X-ray diffractometer at 45°C after 80 cycles. Therefore, the interplanar spacing change rate of the positive electrode active material before and after the cycle is small, indicating that the crystal structure stability of the positive electrode active material is good. During the long-term cycle of the battery, the positive electrode active material is not easy to pulverize, which can improve the cycle performance of the battery.
[0005] According to some embodiments of the present application, 0.05%≤Δd≤0.3%. Thus, the crystal structure stability of the positive electrode active material is better, which can improve the cycle performance of the battery.
[0006] According to some embodiments of the present application, the cross-sectional porosity P of the positive electrode active material satisfies: 0.5%≤P≤10%, optionally, 1%≤P≤5%. By making the cross-sectional porosity within the above range, it is beneficial to the infiltration of the electrolyte and the use of the capacity, and at the same time, the strength of the positive electrode active material can be improved, the structural stability of the positive electrode active material can be improved, and the cycle performance of the battery can be improved.
[0007] According to some embodiments of the present application, the ball splitting rate ΔB of the positive electrode active material satisfies: 0<ΔB≤60%, optionally, 5%≤ΔB≤40%. By making the ball splitting rate within the above range, the strength of the positive electrode active material is improved, the structural stability of the positive electrode active material is improved, and the cycle performance of the battery is improved.
[0008] According to some embodiments of the present application, 0.8≤x≤0.95. Therefore, the nickel content in the positive electrode active material is relatively high, thereby increasing the gram capacity of the positive electrode active material.
[0009] According to some embodiments of the present application, G includes Al, Y, Zr, W, Sn, Ta, Sr, Mn, Na, Ba, and Li. As a result, the lattice structure of the material is more stable, and the change rate of the interplanar spacing is low, so that the material has better performance in terms of cycles.
[0010] The second aspect of the present application provides a method for preparing the positive electrode active material provided in the first aspect of the present application, the method comprising: 1 The first additive of the element is mixed for the first time, and the rotation speed of the first mixing is R 1 To obtain a first mixture, the first additive includes G 1 Oxides of elements, containing G 1 Hydroxides of elements, containing G 1 At least one of the carbonates of the element; the first mixture and the G 2 The second additive of the element is mixed for the second time, and the rotation speed of the second mixing is R 2 , to obtain the second mixture, R 1 >R 2 The second additive includes G 2 Sulfates of elements, containing G 2 At least one phosphate of an element, G=G 1 +G 2; The second mixture is sintered for the first time and crushed to obtain a first-sintered material; the first-sintered material is mixed with a third additive containing the T element, sintered for the second time, the temperature of the second sintering is lower than the temperature of the first sintering, and crushed to obtain the positive electrode active material. Thus, high-speed physical mixing when adding the first additive can make the first additive evenly distributed on the surface of the material, and then evenly enter the lattice after the first sintering, thereby improving the lattice stability of the positive electrode active material; low-speed physical mixing when adding the second additive can make the second additive stay on the surface of the material or at the grain boundary, and pores can be generated on the material after washing away part of the second additive with water, and some channels can be formed inside the material, which is conducive to the infiltration of the electrolyte, and then helps the material capacity to be exerted.
[0011] According to some embodiments of the present application, 1.1≤R 1 : R 2 ≤8.
[0012] According to some embodiments of the present application, the first sintering includes: heating the second mixture to T 1 ℃, holding time is S 1 h, and continue to heat up to T 2 ℃, holding time is S 2 h, then cooled to room temperature, where 250℃≤T 1 ≤650℃,1h≤S 1 ≤5h, 650℃≤T 2 ≤1000℃,6h≤S 2 ≤12h. Therefore, during the first sintering, through two heat preservations, the lithium source and the first additive can have enough time to react with the precursor at a suitable temperature, and simultaneously generate appropriate pores, thereby improving the particle strength of the positive electrode active material.
[0013] According to some embodiments of the present application, the temperature of the second sintering is T 3 , the holding time is S 3 , and then cooled to room temperature, where 200℃≤T 3 ≤500℃,5h≤S 3 ≤10h. In this way, the second additive can be better combined with the material surface, which helps to improve the surface stability of the material.
[0014] According to some embodiments of the present application, at least one of the following conditions is met: the volume particle size Dv100 of the first additive satisfies: 5μm≤Dv100≤50μm; the volume particle size Dv100 of the second additive satisfies: 50μm≤Dv100≤1000μm. Thus, by making the volume particle size of the first additive within the above range, the first additive can better enter the material lattice, play a role in stabilizing the lattice, and thus improve the material's cycle performance; by making the volume particle size of the second additive within the above range, the second additive can tend to stay on the material surface or at the grain boundary, and after washing away part of the second additive with water, pores can be generated on the material, which is conducive to the infiltration of the electrolyte, thereby improving the material's capacity.
[0015] According to some embodiments of the present application, the method satisfies at least one of the following conditions: 1 The element includes at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, F, and P. Optionally, the G 1 The element includes at least one of Al, Y, Zr, W, Sn, Ta, Sr, and Mn; the G 2 The element includes at least one of Al, Y, Zr, Ca, Na, Ba, Li, Mg, Sr, Mo, and Mn. Optionally, the G 2 The element includes at least one of Al, Y, Na, Ba, and Li.
[0016] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.
[0017] The fourth aspect of the present application provides a battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0018] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 The cross-sectional schematic diagram of the positive electrode active material in Example 1 of the present application under a scanning electron microscope is shown.
[0021] Figure 2 The cross-sectional schematic diagram under a scanning electron microscope is shown after the positive electrode active material in Example 1 of the present application is made into a positive electrode sheet.
[0022] Figure 3 A schematic flow chart of a method for preparing a positive electrode active material according to an embodiment of the present application is shown.
[0023] Description of reference numerals:
[0024] 1 Positive electrode active material; 2 Pores; 3 Cracks. DETAILED DESCRIPTION
[0025] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0026] Multi-electrode active materials have a layered structure. The (104) characteristic peak is an important manifestation of the layered structure. The (104) characteristic peak is closely related to the electrochemical properties of the multi-electrode active materials. For example, good peak shape and intensity mean that the positive electrode active material has a good lithium ion transmission channel and a high crystal structure stability. Lithium ions can be smoothly embedded and extracted during the charge and discharge process, so that the positive electrode active material exhibits good rate performance, high reversible capacity and good cycle performance. Among them, the peak surface spacing of the (104) characteristic peak is closely related to the stability of the layered structure. During the battery charge and discharge process, if the peak surface spacing changes significantly, it will cause the layered structure to distort or collapse, which in turn affects the electrochemical properties of the multi-electrode active material and the cycle performance of the battery.
[0027] In a first aspect, the present application provides a positive electrode active material, wherein the positive electrode active material comprises a compound represented by formula I: Li 1+a (Ni x Co y Mn z G b )T c O 2 Formula I, wherein 0.01≤a≤0.1, 0.6≤x≤1, 0<y≤0.2, 0<z≤0.2, 0<b≤0.04, 0≤c≤0.03; G includes at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, Li, F, and P, and T includes at least one of B, Al, Sr, Si, Nb, W, Ti, Zr, La, F, and P; the characteristic peak interplanar spacing change rate Δd of the positive electrode active material (104) satisfies: 0.05%≤Δd≤0.5%, wherein Δd=(d 前 -d 后 ) / d前 ×100%,d 前 is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by X-ray diffractometer before cycling, d 后 It is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by an X-ray diffractometer at 45°C after 80 cycles.
[0028] The multi-element positive electrode active material proposed in the present application has a small change rate of the crystal plane spacing of the multi-element positive electrode active material before and after the cycle, indicating that the crystal structure stability of the positive electrode active material is good. During the long-term cycle of the battery, the crystal structure can remain relatively stable, reducing the internal stress accumulation and structural damage of the positive electrode active material caused by structural changes, effectively slowing down the attenuation of the battery capacity, and improving the cycle performance of the battery.
[0029] In order to test the change rate Δd of the interplanar spacing of the (104) characteristic peak, the present invention uses an X-ray diffractometer to test the interplanar spacing d of the (104) characteristic peak of the positive electrode active material before assembling it into the battery. 前 The positive electrode active material is then prepared into a slurry and coated onto a positive electrode current collector to form a positive electrode sheet. The positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte are assembled into a battery. The battery is cycled for 80 cycles at 45°C. The battery is disassembled, the positive electrode active material on the positive electrode sheet is scraped off, and the peak spacing d of the (104) characteristic peak of the positive electrode active material is measured by an X-ray diffractometer under the same test conditions. 后 , and then through the formula △d=(d 前 -d 后 ) / d 前 × 100%, calculate the change rate of the interplanar spacing △d.
[0030] As an example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material, a binder and a conductive agent provided in the first aspect of the present application.
[0031] As an example, the type and content of the binder are not particularly limited, and the binder may include one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers, or modified derivatives thereof (eg, carboxylic acid, acrylic acid, acrylonitrile, etc. modified).
[0032] As an example, the type and content of the conductive agent are not particularly limited, and the conductive agent may include one or more of acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotube (CNT), and Ketjen black.
[0033] As an example, the positive electrode current collector can generally be a layer body, and the positive electrode current collector is generally a structure or part that can collect current. The positive electrode current collector can be various materials in the art that are suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can be including but not limited to metal foil, and more specifically can be including but not limited to nickel foil and aluminum foil.
[0034] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material is a conventional choice in the battery field, and the type and content are not specifically limited, and can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate, or other metals that can form alloys with lithium.
[0035] Among them, the graphite may include one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys.
[0036] The negative electrode current collector is generally a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium secondary batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, more specifically can include but is not limited to copper foil. In addition, the negative electrode plate can also be a lithium plate.
[0037] As an example, the isolation membrane is a common choice in the battery field. The type and content are not specifically limited and can be one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0038] As an example, the electrolyte is a conventional choice in the battery field, and the type and content are not specifically limited. It can be various electrolytes suitable for lithium secondary batteries in the field. For example, the electrolyte generally includes an electrolyte and a solvent. The electrolyte generally includes a lithium salt. More specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, and specifically can include but is not limited to LiPF 6 , LiBF 4 、LiN(SO 2 F) 2 (abbreviated as LiFSI), LiN(CF 3 SO 2 ) 2 (abbreviated as LiTFSI), LiClO 4 、LiAsF 6、LiB(C 2 O 4 ) 2 (abbreviated as LiBOB), LiBF 2 C 2 O 4 (abbreviated as LiDFOB) or more.
[0039] As an example, Δd may be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc., or may be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.05%≤Δd≤0.3%.
[0040] According to some embodiments of the present application, the cross-sectional porosity P of the positive electrode active material satisfies: 0.5% ≤ P ≤ 10%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or it can be a range composed of any of the above numerical values. Therefore, when the (104) characteristic peak interplanar spacing change rate △d and the cross-sectional porosity P are in the above range, on the one hand, the positive electrode active material has good crystal structure stability, and the crystal structure of the positive electrode active material can remain relatively stable during the battery charging and discharging process, thereby improving the overall cycle performance of the battery; on the other hand, the contact area between the electrolyte and the positive electrode is large, which is conducive to the electrolyte infiltration of the positive electrode and the exertion of capacity. According to some specific embodiments of the present application, 1% ≤ P ≤ 5%.
[0041] In this application, the test method of cross-sectional porosity P is: the positive electrode active material is cut by an ion cutting method, and the cross-sectional morphology is photographed by a scanning electron microscope. Figure 1 , there are a plurality of pores 2 on the cross section of the positive electrode active material 1. The percentage of the total area of the pores on the cross section to the total area of the cross section is calculated using intelligent analysis software for lithium-ion battery material microscopic images.
[0042] It should be noted that the cross section referred to here refers to the porosity of the cross section corresponding to the cross section diameter in the SEM image when it is the same as the Dv50 of the positive electrode active material.
[0043] According to some embodiments of the present application, the ball splitting rate △B of the positive electrode active material satisfies: 0<△B≤60%, for example, it can be 2%, 5%, 10%, 20%, 40%, 60%, etc., or it can be a range composed of any of the above values. When the ball splitting rate of the positive electrode active material is within the above range, the strength of the positive electrode active material can be improved, and the positive electrode active material can maintain its original morphology during the battery charging and discharging process, thereby improving the cycle stability of the positive electrode active material and improving the cycle performance of the battery. According to some specific embodiments of the present application, 5%≤△B≤40%.
[0044] In the present application, the test method of the ball splitting rate △B is: the positive electrode active material proposed in the present application is mixed with the small-particle positive electrode active material, and the mixing ratio is 1:9-9:1. The small-particle positive electrode active material is a lithium-ion battery positive electrode material such as lithium nickel cobalt manganese oxide and lithium iron phosphate in the form of single crystal or polycrystalline. The volume average particle size Dv50 of the small-particle positive electrode active material is 1μm-7μm. The positive electrode active material, the conductive agent and the binder are mixed, slurried, coated and dried according to (90%-99%): (0.5%-6%): (0.5%-5%) to obtain a positive electrode sheet, and a roller press is used to press the positive electrode sheet to a compaction density of 3.5g / cm 3 The rolled positive electrode sheet was cut by ion cutting method, and the cross-section morphology was photographed by scanning electron microscope. Figure 2 After rolling, cracks appear in some positive electrode active materials 3. Five pictures at different positions are taken under 1k conditions. The ratio of the number of cracked particles to the total number of particles in each picture is calculated. The average value of the results of the five pictures is △B.
[0045] As an example, a may be 0.01, 0.05, 0.1, etc., or may be a range consisting of any of the above values.
[0046] As an example, x can be 0.6, 0.7, 0.8, 0.9, 1, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.8≤x≤0.95.
[0047] As an example, y may be 0.05, 0.1, 0.15, 0.2, etc., or may be a range consisting of any of the above values.
[0048] As an example, z may be 0.05, 0.1, 0.15, 0.2, etc., or may be a range consisting of any of the above values.
[0049] As an example, b may be 0.01, 0.02, 0.03, 0.04, etc., or may be a range consisting of any of the above values.
[0050] As an example, c may be 0, 0.01, 0.02, 0.03, etc., or may be a range consisting of any of the above values.
[0051] As examples, G may include one or more of Al, Y, Zr, W, Sn, Ta, Sr, Mn, Na, Ba, and Li.
[0052] The second aspect of the present application provides a method for preparing the positive electrode active material provided in the first aspect of the present application, the method comprising: 1 The first additive of the element is mixed for the first time, and the rotation speed of the first mixing is R1 To obtain a first mixture, the first additive includes G 1 Oxides of elements, containing G 1 Hydroxides of elements, containing G 1 At least one of the carbonates of the element; the first mixture and the G 2 The second additive of the element is mixed for the second time, and the rotation speed of the second mixing is R 2 , to obtain the second mixture, R 1 >R 2 The second additive includes G 2 Sulfates of elements, containing G 2 At least one phosphate of an element, G=G 1 +G 2 ; The second mixture is sintered for the first time and crushed to obtain a first-sintered material; the first-sintered material is mixed with a third additive containing a T element and sintered for the second time, the temperature of the second sintering is lower than the temperature of the first sintering, and the material is crushed to obtain the positive electrode active material. Thus, high-speed physical mixing when adding the first additive can make the first additive evenly distributed on the surface of the material, and evenly enter the material lattice after the first sintering, thereby playing a role in stabilizing the lattice. Low-speed physical mixing when adding the second additive can make the second additive stay on the surface of the material or at the grain boundary. After washing with water to wash away part of the second additive, pores can be generated on the material, which is conducive to the infiltration of the electrolyte, thereby improving the performance and capacity of the material. After the battery is cycled, the change rate of the interplanar spacing of the characteristic peak of the positive electrode active material (104) can be reduced, thereby improving the stability of the crystal structure of the positive electrode active material and improving the cycle performance of the battery.
[0053] The following is a detailed description of this method, see Figure 3 , the method comprising:
[0054] S10: Ni-Co-Mn precursor, lithium source, G 1 The first additive of the element is mixed for the first time, and the rotation speed of the first mixing is R 1 To obtain a first mixture, the first additive includes G 1 Oxides of elements, containing G 1 Hydroxides of elements, containing G 1 At least one of the carbonates of the element
[0055] According to some embodiments of the present application, a nickel-cobalt-manganese precursor, a lithium source, and a G-containing 1 The first additive of the element is physically mixed at high speed to obtain a uniform first mixture containing G 1 Oxides of elements, containing G 1 Hydroxides of elements, containing G1 At least one of the carbonates of the elements can be physically mixed at high speed so that the first additive is evenly distributed on the surface of the material, and can evenly enter the interior of the material lattice after sintering, thereby improving the lattice stability of the positive electrode active material.
[0056] According to some embodiments of the present application, 1.1≤R 1 : R 2 ≤ 8. For example, it may be 1.1, 3, 5, 7, 8, etc., or may be a range consisting of any of the above values.
[0057] As an example, when a high-speed mixer is used for mixing, 600rpm≤R 1 ≤1000 rpm. For example, it may be 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc., or may be a range consisting of any of the above values.
[0058] According to some embodiments of the present application, n (lithium element in the lithium source): n (nickel cobalt manganese element in the nickel cobalt manganese precursor) = (1.01-1.1): 1, for example, it can be 1.01:1, 1.03:1, 1.05:1, 1.07:1, 1.1:1, etc., or it can be a range consisting of any of the above values.
[0059] According to some embodiments of the present application, the G 1 The elements include at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, F, and P.
[0060] According to some embodiments of the present application, the G 1 The element includes at least one of Al, Y, Zr, W, Sn, Ta, Sr, and Mn.
[0061] According to some embodiments of the present application, the nickel-cobalt-manganese precursor includes one or both of nickel-cobalt-manganese oxide or nickel-cobalt-manganese hydroxide.
[0062] According to some embodiments of the present application, the lithium source includes one or more of lithium carbonate, aqueous lithium hydroxide, or anhydrous lithium hydroxide.
[0063] According to some embodiments of the present application, the volume particle size Dv100 of the first additive satisfies: 5 μm≤Dv100≤50 μm.
[0064] S20: mixing the first mixture and the 2 The second additive of the element is mixed for the second time, and the rotation speed of the second mixing is R 2 , to obtain the second mixture, R1 >R 2 The second additive includes G 2 Sulfates of elements, containing G 2 At least one phosphate of an element, G=G 1 +G 2
[0065] When adding the second additive, physical mixing at a low speed can make the second additive remain on the surface of the material or at the grain boundary. After washing away part of the additive through water, some pores are generated on the material, which is conducive to the infiltration of the electrolyte and further improves the capacity of the material.
[0066] As an example, when a high-speed mixer is used for mixing, 200rpm≤R 1 ≤600 rpm. For example, it may be 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, etc., or may be a range consisting of any of the above values.
[0067] According to some embodiments of the present application, the volume particle size Dv100 of the second additive satisfies: 50 μm ≤ Dv100 ≤ 1000 μm. For example, it may be 50 μm, 100 μm, 300 μm, 500 μm, 700 μm, 900 μm, 1000 μm, etc., or may be a range consisting of any of the above values.
[0068] According to some embodiments of the present application, the G 2 The element includes at least one of Al, Y, Zr, Ca, Na, Ba, Li, Mg, Sr, Mo, and Mn.
[0069] According to some embodiments of the present application, the G 2 The element includes at least one of Al, Y, Na, Ba, and Li.
[0070] According to some embodiments of the present application, the second mixture can be washed with water after the second mixing. The solid-liquid ratio of the water washing can be 1:1, and the washing time can be 3min-10min. It is then filtered using a funnel and dried in a vacuum drying oven.
[0071] S30: sintering the second mixture for the first time and crushing it to obtain a first-sintered material
[0072] According to some embodiments of the present application, the second mixture is sintered for the first time in an oxygen atmosphere, and after sintering, the mixture is crushed and screened or directly screened to obtain a fired material.
[0073] According to some embodiments of the present application, the first sintering includes: heating the second mixture to T1 ℃, holding time is S 1 h, and continue to heat up to T 2 ℃, holding time is S 2 h, then cooled to room temperature, where 250℃≤T 1 ≤650℃,1h≤S 1 ≤5h, 650℃≤T 2 ≤1000℃,6h≤S 2 ≤12h.
[0074] As an example, T 1 The temperature may be 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, etc., or may be in a range consisting of any of the above values.
[0075] As an example, S 1 It can be 1h, 2h, 3h, 4h, 5h, etc., or can be a range consisting of the above arbitrary values.
[0076] As an example, T 2 The temperature may be 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., or may be within a range consisting of any of the above values.
[0077] As an example, S 2 It can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc., or can be a range consisting of the above arbitrary numerical values.
[0078] By introducing two heat preservation processes during the first sintering process, the lithium source and the first additive are given enough time to react with the precursor at a suitable temperature, thereby simultaneously generating appropriate pores and improving the particle strength of the material.
[0079] S40: Mixing the first sintered material with a third additive containing the T element, performing a second sintering, wherein the temperature of the second sintering is lower than the temperature of the first sintering, and crushing to obtain the positive electrode active material
[0080] According to some embodiments of the present application, the first-fired material is mixed with a third additive containing the T element and sintered for a third time in an air or oxygen atmosphere. After sintering, the material is crushed and sieved or directly sieved to obtain a positive electrode active material.
[0081] According to some embodiments of the present application, the temperature of the second sintering is T 3 , the holding time is S 3 , then cooled to room temperature, and satisfying 200℃≤T 3 ≤500℃,5h≤S 3≤10h.
[0082] As an example, T 3 The temperature may be 200° C., 300° C., 400° C., 500° C., etc., or may be within a range consisting of any of the above values.
[0083] As an example, it can be 5h, 6h, 7h, 8h, 9h, 10h, etc., or can be a range consisting of the above arbitrary numerical values.
[0084] In summary, the positive electrode active material and the preparation method thereof proposed in this application have the following advantages:
[0085] ① The multi-element positive electrode active material proposed in this application has good crystal structure stability, and the change rate of the crystal plane spacing of the positive electrode active material during battery charging and discharging is small, which can effectively slow down the attenuation of battery capacity and improve the cycle performance of the battery.
[0086] ② The multi-element positive electrode active material proposed in this application has a suitable cross-sectional porosity, which is more conducive to the infiltration of the electrolyte into the positive electrode and can improve the battery capacity.
[0087] ③ The positive electrode active material proposed in this application has high strength, is not easy to break during the battery charging and discharging process, has better structural stability, and can improve the battery's cycle performance.
[0088] ④ The method for preparing positive electrode active materials proposed in the present application adopts high-speed physical mixing to add the first additive, so that the first additive can be evenly distributed on the surface of the material. After the first sintering, it enters the interior of the crystal lattice to stabilize the crystal lattice; the second additive is added by low-speed physical mixing, so that the second additive can only stay on the surface of the material or at the grain boundary. After washing away part of the second additive with water, pores can be generated on the material, which is conducive to the infiltration of the electrolyte, thereby improving the capacity of the material.
[0089] ⑤ The method for preparing positive electrode active materials proposed in this application, during the first sintering process, by keeping the second mixture warm twice, the lithium source, the first additive, and the second additive have enough time to react with the precursor at a suitable temperature, and simultaneously generate appropriate pores to improve the particle strength of the material.
[0090] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.
[0091] The fourth aspect of the present application provides a battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0092] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application.
[0093] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0094] Example 1
[0095] 1. Preparation of positive electrode active materials
[0096] The precursor (Ni 0.8 Co 0.1 Mn 0.1 )(OH) 2 , lithium hydroxide, SrO 2 and ZrO 2 High-speed physical mixing is carried out by using a high-speed mixer. 1 The first mixture is obtained by rotating the rotating speed at 700 rpm, wherein the amounts of the precursor, lithium hydroxide, Y2O3 and ZrO2 are such that n(Li):[n(Ni)+n(Co)+n(Mn)+n(Y)+n(Zr)]=1.05, n(Y):[n(Ni)+n(Co)+n(Mn)+n(Y)+n(Zr)]=0.008, and n(Zr):[n(Ni)+n(Co)+n(Mn)+n(Y)+n(Zr)]=0.003 in the positive electrode active material;
[0097] (2) Using a high speed mixer to mix the first mixture and Al 2 (SO 4 ) 3 Perform low speed physical uniform mixing, R 2 The second mixture is obtained at 600 rpm, wherein Al 2 (SO 4 ) 3 The amount used is such that n(Al) in the positive electrode active material: [n(Ni)+n(Co)+n(Mn)+n(Y)+n(Zr)+n(Al)]=0.002,
[0098] (2) In an oxygen atmosphere, the second mixture is subjected to a first sintering, wherein the specific heating curve is as follows: heating to 350° C. for 2 h, keeping the temperature for 2 h, heating to 790° C. for 5 h, keeping the temperature for 10 h, and then cooling down. After sintering, the mixture is crushed and sieved or directly sieved to obtain a first-fired material;
[0099] (3) washing the calcined material with water at a solid-liquid ratio of 1:1 for 5 minutes, then filtering with a funnel, and finally drying in a vacuum oven;
[0100] (4) The dried first-fired material was mixed with boric acid according to [n(Ni)+n(Co)+n(Mn)+n(Y)+n(Zr)+n(Al)]:n(B)=1:0.005, and a second sintering was performed. The sintering atmosphere was air, the constant temperature was 300°C, and the constant temperature time was 10h. After sintering, it was directly sieved to obtain the final positive electrode active material with a composition of Li 1.05 (Ni 0.8 Co 0.1 Mn 0.1 Y 0.008 Zr 0.003 Al 0.002 )B 0.005 O 2 .
[0101] 2. Preparation of positive electrode sheet
[0102] The positive electrode active material Li 1.05 (Ni 0.8 Co 0.1 Mn 0.1 Y 0.008 Zr 0.003 Al 0.002 )B 0.005 O 2 9.5g of acetylene black, 0.25g of acetylene black and 0.25g of polyvinylidene fluoride (PVDF) were mixed to form a positive electrode slurry, which was coated on an aluminum foil and dried, and then pressed with a pressure of 100MPa to form a 12mm diameter and 120μm thickness, and then dried in a vacuum drying oven at 120℃ for 12h to obtain a positive electrode sheet.
[0103] 3. Preparation of negative electrode sheet
[0104] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm.
[0105] 4. Isolation film
[0106] A polyethylene porous film having a thickness of 25 μm was used as the separator.
[0107] 5. Preparation of Electrolyte
[0108] Using 1.0 mol / L LiPF 6 The solution is an electrolyte, in which an equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) is used as a solvent.
[0109] 6. Assemble the battery
[0110] The positive electrode plate, the separator, the negative electrode plate and the electrolyte are assembled into a 2025 button battery.
[0111] The preparation process of the positive electrode active materials in Examples 2 to 14 and Comparative Examples 1 to 4 is the same as that in Example 1, and the differences are detailed in Tables 1 and 2.
[0112]
[0113]
[0114]
[0115]
[0116] Performance Testing
[0117] 1. Change rate of characteristic peak interplanar spacing of multi-electrode active materials (104)
[0118] Before the positive electrode active material is assembled into the battery, the peak spacing d of the (104) characteristic peak of the positive electrode active material is obtained by X-ray diffractometer test. 前 The positive electrode active material is then prepared into a slurry and coated onto a positive electrode current collector to form a positive electrode sheet. The positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte are assembled into a battery. The battery is cycled for 80 cycles at 45°C. The battery is disassembled, the positive electrode active material on the positive electrode sheet is scraped off, and the peak spacing d of the (104) characteristic peak of the positive electrode active material is measured by an X-ray diffractometer under the same test conditions. 后 , and then through the formula △d=(d 前 -d 后 ) / d 前 × 100%, calculate the change rate of the interplanar spacing △d.
[0119] Battery cycle conditions:
[0120] The battery sample was charged and discharged twice at a current density of 20mA / g, with a voltage range of 3.0V-4.3V, and activation was completed. The activated battery sample was used to perform a specified number of charge and discharge cycles at a temperature of 45°C, with a current density of 1C in a voltage range of 3.0-4.3V.
[0121] 2. Cross-sectional porosity P of multi-element positive electrode active materials
[0122] The positive electrode active material was cut by an ion cutting method, the cross-sectional morphology was photographed by a scanning electron microscope, and the percentage of the total area of pores on the cross section to the total area of the cross section was calculated using intelligent analysis software for lithium-ion battery material microscopic images.
[0123] 3. The cracking rate of multi-element positive electrode active materials △B
[0124] The positive electrode active material and the small particles of positive electrode active material (8 series single crystal Li 1.02 (Ni 0.8 Co 0.1 Mn 0.1 ) 2 ) are mixed at a mixing ratio of 7:3, the volume average particle size Dv50 of the small particles of the positive electrode active material is 3.5μm, the positive electrode active material, conductive carbon black, carbon nanotubes and binder polyvinylidene fluoride (PVDF) are mixed at a ratio of 97%: 1%: 0.5%: 1.5%, slurried, coated, and dried to obtain a positive electrode sheet, which is pressed by a roller press to a compaction density of 3.5g / cm 3 The rolled positive electrode sheet was cut by ion cutting method, and the cross-sectional morphology was photographed by scanning electron microscope. Five pictures were taken at different positions under 1k conditions, and the ratio of the number of cracked particles to the total number of particles in each picture was calculated. The average value of the results of the five pictures was taken as △B.
[0125] 4. Capacity
[0126] Capacity test conditions: The prepared button cell samples were placed for 24 hours. The battery samples were charged at a current density of 20 mA / g to a cut-off voltage of 4.3 V. The battery samples were charged at a constant voltage of 4.3 V for 30 minutes. Then, the battery samples were discharged at a current density of 20 mA / g to a cut-off voltage of 3.0 V. The discharge time was recorded.
[0127] The initial discharge specific capacity of the battery sample = current density × discharge time.
[0128] 5. Capacity retention rate after 80 cycles
[0129] The cycle conditions were as described above, and 80 cycles were performed. The discharge specific capacity of each charge and discharge cycle was obtained by comparing the current density with the discharge time of each cycle. The cycle performance of the 80th discharge specific capacity battery sample was characterized by the high temperature capacity retention rate.
[0130] Capacity retention rate after 80 cycles = (discharge specific capacity at the 80th cycle / discharge specific capacity at the 1st cycle) × 100%.
[0131] The test results of the positive electrode active materials and batteries in Examples 1 to 14 and Comparative Examples 1 to 4 are shown in Table 3.
[0132] Table 3
[0133]
[0134]
[0135] It can be seen from the comparison between Examples 1 to 14 and Comparative Examples 1 to 4 that the battery prepared using the positive electrode active material proposed in the present application can have both a higher capacity and a higher cycle capacity retention rate, indicating that by controlling the change rate of the crystal plane spacing of the positive electrode active material, a positive electrode active material with better crystal structure stability can be obtained, which can effectively slow down the attenuation of the battery capacity during the battery cycle and improve the battery cycle performance.
[0136] It can be seen from the comparison between Examples 1 to 4 and Comparative Examples 2 to 4 that in the process of preparing the positive electrode active material, by adding the first additive under high-speed stirring and adding the second additive under low-speed stirring, a positive electrode active material with a stable crystal structure and a small rate of change of interplanar spacing can be obtained, thereby obtaining a battery with high capacity and high cycle capacity retention rate.
[0137] It can be seen from Examples 5 to 7 that adding different types of first additives by high-speed stirring and adding different types of second additives by low-speed stirring can improve the lattice stability of the positive electrode active material and reduce the rate of change of the interplanar spacing, thereby obtaining a battery with high capacity and high cycle capacity retention rate.
[0138] It can be seen from Examples 8 to 10 that in the process of preparing the positive electrode active material, by adopting two heat preservation processes during the first sintering, the lithium source, the precursor, the first additive and the second additive can be fully reacted, and the change rate of the crystal plane spacing of the positive electrode active material can be reduced. At the same time, the positive electrode active material has appropriate porosity, the particle strength of the positive electrode active material is improved, and the cracking rate of the positive electrode active material is reduced, thereby obtaining a battery with high capacity and high cycle capacity retention rate.
[0139] It can be seen from Examples 11 and 12 that by adopting the mixing method of the first additive and the second additive and the sintering method proposed in the present application, when using the first additive and the second additive of different element types, a positive electrode active material with a small crystal plane spacing change rate, moderate porosity, and low ball cracking rate can be obtained, thereby obtaining a battery with high capacity and high cycle capacity retention rate.
[0140] It can be seen from Example 13 and Example 14 that when the nickel content in the precursor is different, the mixing method of the first additive and the second additive and the sintering method proposed in this application can also obtain a positive electrode active material with a small crystal plane spacing change rate, moderate porosity, and low ball cracking rate, thereby obtaining a battery with high capacity and high cycle capacity retention rate.
[0141] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: Including compounds shown in formula I: Li 1+a (Ni x Co y Mn z G b )T c O₂ type Ι, Wherein, 0.01≤a≤0.1, 0.6≤x≤1, 0<y≤0.2, 0<z≤0.2, 0<b≤0.04, 0≤c≤0.03; G includes at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, Li, F, and P, and T includes at least one of B, Al, Sr, Si, Nb, W, Ti, Zr, La, F, and P; The characteristic peak interplanar spacing change rate Δd of the positive electrode active material (104) satisfies: 0.05%≤Δd≤0.5%, wherein Δd=(d 前 -d 后 ) / d 前 ×100%,d 前 is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by X-ray diffractometer before cycling, d 后 It is the interplanar spacing of the characteristic peak of the positive electrode active material (104) measured by an X-ray diffractometer at 45°C after 80 cycles.
2. The positive electrode active material according to claim 1, characterized in that 0.05%≤△d≤0.3%。 3. The positive electrode active material according to claim 2, characterized in that The cross-sectional porosity P of the positive electrode active material satisfies: 0.5%≤P≤10%, optionally, 1%≤P≤5%.
4. The positive electrode active material according to claim 3, characterized in that The ball cracking rate ΔB of the positive electrode active material satisfies: 0<ΔB≤60%, optionally, 5%≤ΔB≤40%.
5. The positive electrode active material according to claim 1, characterized in that 0.8≤x≤0.95。 6. The positive electrode active material according to claim 1, characterized in that G includes at least one of Al, Y, Zr, W, Sn, Ta, Sr, Mn, Na, Ba, and Li.
7. A method for preparing the positive electrode active material according to any one of claims 1 to 6, characterized in that: include: The nickel-cobalt-manganese precursor, the lithium source, and the first additive containing the G1 element are mixed for the first time, and the rotation speed of the first mixing is R1 to obtain a first mixture, wherein the first additive includes at least one of an oxide containing the G1 element, a hydroxide containing the G1 element, and a carbonate containing the G1 element; The first mixture and the second additive containing the G2 element are mixed for the second time, the rotation speed of the second mixing is R2, to obtain a second mixture, R1>R2, the second additive includes at least one of a sulfate containing the G2 element and a phosphate containing the G2 element, G=G1+G2; sintering the second mixture for the first time and crushing it to obtain a first-burned material; The first-sintered material is mixed with a third additive containing the T element, and is subjected to a second sintering, wherein the temperature of the second sintering is lower than the temperature of the first sintering, and is crushed to obtain the positive electrode active material.
8. The method according to claim 7, characterized in that 1.1≤R1:R2≤8.
9. The method according to claim 8, characterized in that The first sintering includes: heating the second mixture to T1°C, keeping the temperature for S1h, continuing to heat the second mixture to T2°C, keeping the temperature for S2h, and then cooling the temperature to room temperature, wherein 250°C≤T1≤650°C, 1h≤S1≤5h, 650°C≤T2≤1000°C, and 6h≤S2≤12h.
10. The method according to claim 9, characterized in that The second sintering temperature is T3, the holding time is S3, and then the temperature is reduced to room temperature, and 200°C≤T3≤500°C, 5h≤S3≤10h are satisfied.
11. The method according to claim 10, characterized in that Satisfy at least one of the following conditions: The volume particle size Dv100 of the first additive satisfies: 5 μm≤Dv100≤50 μm; The volume particle size Dv100 of the second additive satisfies: 50 μm≤Dv100≤1000 μm.
12. The method according to claim 10, characterized in that Satisfy at least one of the following conditions: The G1 element includes at least one of Al, Y, Zr, Ti, Ca, Na, Nb, Sn, Ta, Co, W, Er, La, Sb, Mg, Sr, Mo, Mn, Ce, F, and P. Optionally, the G1 element includes at least one of Al, Y, Zr, W, Sn, Ta, Sr, and Mn; The G2 element includes at least one of Al, Y, Zr, Ca, Na, Ba, Li, Mg, Sr, Mo, and Mn. Optionally, the G2 element includes at least one of Al, Y, Na, Ba, and Li.
13. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 6 or the positive electrode active material prepared by the method according to any one of claims 7 to 12.
14. A battery, characterized in that: Including the positive electrode sheet as described in claim 13.
15. An electrical equipment, characterized in that: Comprising the battery of claim 14.
Citation Information
Cited By
Positive electrode active material and preparation method thereof, positive electrode plate and battery
CN121260795A
Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
CN121394362A
Positive electrode active material, preparation method therefor, positive electrode sheet, battery, and electrical device
WO2026091396A1
Positive electrode material and preparation method therefor, battery and electric device
WO2026178947A1